Studi Literatur: Hubungan Kunjungan Anc Terhadap Kemampuan Deteksi Tanda Bahaya Kehamilan - Ishak, Fifi; Ali, Rizky Nikmathul Husna; Asikin, Zulaika F (Madu : Jurnal Kesehatan, 2023)
There are various danger signs of pregnancy in the 1st trimester (0-12 weeks) including excessive nausea, vomiting, and persistent headaches, blurred vision, anemia and high fever. In the 12th trimester (12-27 weeks) the danger signs of pregnancy include vaginal bleeding, severe abdominal pain and lack of fetal movement. And in the 3rd trimester (27-36 weeks), including swelling of the face, feet and hands, premature discharge of amniotic fluid and vaginal bleeding (Pratiwi, 2019). Lack of knowledge of mothers and families in recognizing danger signs of pregnancy will cause delays in reaching access to health services, leading to death in mothers (Brahma, 2018).The objective of research was to determine the relationship between ANC visits and the ability to recognize pregnancy danger signs. The results from five journals that meet the inclusion criteria, the factors that influence the ANC visit to the recognition of pregnancy danger signs are obtained, namely knowledge, attitudes and motivation. The conclusion, there is a relationship between ANC visits and danger signs of pregnancy in terms of knowledge and attitudes.